Exploratory Biomarker Study of the Triple Reuptake Inhibitor SEP‐432 Compared to the Dual Reuptake Inhibitor Duloxetine in Healthy Normal Subjects. (5th February 2016) - Sramek, John J.; Hardy, Larry W.; Bieck, Peter; Zamora, Cynthia; Versavel, Mark; Kharidia, Jahnavi; Grinnell, Todd; Chen, Yu‐Luan; Sullivan, Michael; Ding, Hong; Cutler, Neal R.
Summary: Introduction: SEP‐432 is a triple monoamine reuptake inhibitor of norepinephrine (NE), serotonin (5‐HT), and dopamine (DA), based on in vitro binding studies. We sought evidence that SEP‐432 engages these monoamine systems by measuring concentrations of monoamines and/or their main metabolites in cerebrospinal fluid (CSF) and plasma and comparing results to duloxetine, a dual reuptake inhibitor of NE and 5‐HT. Methods: Eighteen healthy normal subjects received either SEP‐432 (300 mg/day), duloxetine (60 mg/day), or placebo for 14 days in‐clinic (double blind) with CSF and plasma collections at baseline (single lumbar puncture) and Day 14 (24‐h CSF and plasma collection). Concentrations of monoamines and their metabolites, as well as pharmacokinetic concentrations of SEP‐432 and metabolite, were quantified by liquid chromatography–tandem mass spectrometry. Results: Compared to placebo in the Day 14 area under the curve 24‐h (AUC0–24 h ) analysis, SEP‐432 significantly ( P  < 0.05) decreased the NE metabolite dihydroxyphenylglycol (DHPG) in CSF and plasma, decreased 5‐HT in plasma, and did not affect DA metabolites, while duloxetine had significant effects on DHPG and 5‐HT. Time‐matched baseline to Day 14 biomarker comparisons confirmed these findings. Conclusion: CSF monoamine biomarkers confirmed central NET activity for SEP‐432 and duloxetine's dual reuptake inhibition.